The Top-20 Studies About Anterior Shoulder Instability From an Altmetric Analysis Had Higher Levels of Evidence Than Those From a Traditional Bibliometric Analysis - Liam O'Dwyer, B.Sc; Conor Ledingham, M.B., B.Ch., M.Ch; Martin S. Davey, M.B., B.Ch., B.A.O., M.Ch., M.R.C.S; Austin Kerin, B.Sc; Azim Huszar, B.Sc; J. Tristan Cassidy, M.B., B.Ch., M.Ch., F.R.C.S.I. (Tr & Orth) (Elsevier, 2024)
Purpose: To compare the characteristics of the top-20 studies about anterior shoulder instability according to the Altmetric Attention Score (AAS) with total citation counts. Methods: Two separate searches were performed for articles related to anterior shoulder instability. The Altmetric search identified the top-20 articles according to AAS. A bibliometric search using Web of Science identified the top-20 most-cited articles. Altmetric criteria were applied to the bibliometric list and vice versa. Results: The AAS from the Altmetric list ranged from 44 to 432. The highest AAS from the bibliometric search was 70. One study appeared in both lists. Most online mentions were from X (formerly Twitter). The geographical breakdown of X mentions saw 71 countries appearing in the Altmetric search versus 21 in the bibliometric search. The total citations in the bibliometric list ranged from 91 to 358 versus 0 to 121 for the Altmetric list. The Altmetric top-20 list contained 8 studies that were Level II or higher versus 3 in the bibliometric list. Conclusions: The top-20 studies according to AAS or citation count are not the same. The top-20 studies by AAS are composed of studies at higher levels of evidence versus the top-20 studies when listed by citation count. Clinical Relevance: Electronic searches are an important way to access information in the modern world. Different search options generate results according to different parameters and may generate different results for the same query. It is important to understand these differences so that users have a better understanding of where the most clinically useful information can be found, especially regarding medical conditions.